1987
DOI: 10.1016/s0022-5347(17)44214-5
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Calcium, Calcium Channel Blockers and Bay K 8644 on Contractions Induced by Muscarinic Receptor Stimulation of Isolated Bladder Muscle from Rabbit and Man

Abstract: In isolated bladder smooth muscle from both rabbit and man, carbachol-induced contractions were reduced by the calcium channel blocker nifedipine, whereas the calcium channel promotor Bay K 8644 had no effect. In nominally calcium-free medium containing 10(-4) M EGTA, carbachol-induced contractions were reduced by 69% (rabbit) and 87% (man). These contractions were abolished by nifedipine, whereas Bay K 8644 significantly increased their amplitude, in rabbit preparations almost to control level. Electrical fie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…Fovaeus et al, 1987). This could occur through activation of receptor-operated mechanisms as proposed for many other smooth muscles (Somlyo & Somlyo, 1968;Bolton, 1979).…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Fovaeus et al, 1987). This could occur through activation of receptor-operated mechanisms as proposed for many other smooth muscles (Somlyo & Somlyo, 1968;Bolton, 1979).…”
Section: Discussionmentioning
confidence: 94%
“…In vivo studies in anaesthetized rats suggested that Ca mobilization via nifedipineresistant pathways might be a relevant mode of contraction during a physiological-like event, that is, volume-evoked bladder voiding (micturition reflex) (Maggi et al, 1988a). Fovaeus et al (1987) investigated the effect of nifedipine and Bay K 8644 on carbachol-induced contractions of human isolated bladder muscle and concluded that both voltagedependent and receptor-operated Ca channels mediate this response. Recently we studied the effect of endothelin, an endothelium-derived vasconstrictor peptide proposed to act as an endogenous agonist at dihydropyridine-sensitive Ca channels in the human isolated bladder (Maggi et al, 1989a) and found that the contractile response to this peptide was almost totally nifedipine-resistant while the KCI-induced contraction was abolished by nifedipine-pretreatment. These observations prompted us to re-address N02/02 (1/2) and halothane (0.6-1 %).…”
mentioning
confidence: 99%
“…Previous studies have indicated an important role for extracellular calcium in muscarinic receptor activation of the human bladder (Fovaeus et al, 1987), but the sources of calcium used for contractile activation have been a matter of debate (Andersson 1993). As pointed out by Hashitani et al (2000), in most studies of the contribution of IP 3 production to muscarinic receptormediated contractions in the detrusor, relatively high concentrations of muscarinic receptor agonists have been used.…”
Section: Peripheral Targetsmentioning
confidence: 99%
“…The effect of magnesium in the presence of calcium chan nel ligands supports the hypothesis that magnesium in hibits calcium transport via the calcium channels [14], Verapamil and BAY-K8644 both work on voltagedependent calcium channels. Calcium channel blockers including verapamil inhibit the calcium influx through calcium channels on the smooth muscle cell membrane, which results in decrease in the detrusor contraction induced by both intramural nerve stimulation and direct cholinergic receptor stimulation [21,22], However, BAY-K8644, which is believed to prolong the opening time of…”
Section: Discussionmentioning
confidence: 99%